The Sustainability of a Workplace Wellness Program That Incorporates Gamification Principles: Participant Engagement and Health Benefits After 2 Years. Issue 6 (July 2019) - Lowensteyn, Ilka; Berberian, Violette; Berger, Claudie; Da Costa, Deborah; Joseph, Lawrence; Grover, Steven A.
Purpose: To evaluate the results of a workplace wellness program that incorporates gamification principles. Design: In this prospective cohort study, the participation rate and observed health outcomes were evaluated after approximately 2 years. Setting and participants: All permanent employees (n = 775) of a national company located in Canada were eligible to participate. Intervention: The wellness program included web-based challenges (team or individual) incorporating gamification strategies to improve exercise, nutrition, weight reduction, and mental health management behaviors. Measures and analysis: The primary outcomes were employee participation rates. The secondary pre-specified outcomes were the sustained benefits of the program on physical and mental health measures. Results: Participation rates in the health screenings were 78% (baseline), 54% (year 1), and 56% (year 2). Participation in the 4 team web-based challenges ranged from 33% to 68% with 76% to 86% of participants tracking their activity on at least half of the days. After 2 years, there were significant clinical improvements in systolic blood pressure (−1.3mm Hg), total cholesterol/high-density lipoprotein (HDL) ratio (−0.14), glycated haemoglobin (HbA1c ; −0.1%), weekly physical activity (+264 Metabolic Equivalents [METs]), perceived stress score (−17%), insomnia severity index (−16%), general fatigue (−10%), and reductions in the cardiovascular age gap (−0.3 years). Greater benefits occurred among employees at higher risk. Conclusions: Workplace wellness programs that evolve over time and focus primarily on fun and competitive challenges may support long-term participation, behavior change, and sustained improvements in clinical outcomes.